Governing parameters on xylanase production using developed biorector - Lee, C.K.; Ibrahim, D.; Omar, I.C. (Universiti Sains Malaysia, 2015)
Chemicals bleaching are common steps in pulp and paper manufacturing process. The reduction of chemical use would result in lower waste treatment costs while minimizes the impact on the environment. This can be achieved using enzyme (xylanase). Compared to submerged fermentation process, the cost for enzyme production is much cheaper using solid state fermentation process (SSF). The present study aimed to examine factors affect xylanase production using developed SSF bioreactor. Methodology and results: The performance of developed bioreactor namely FERMSOSTAT had been investigated in xylanase production studies. In this studies, local isolate Aspergillus niger USM AI 1 was used together with sugarcane bagasse and palm kernel cake (ratio 1:1), which serve as substrates for xylanase production. The highest xylanase activity and production of 397 U/g and 103 U/mgG glucosamine were obtained, respectively when the fermentation process was carried out under examined enzyme production conditions of 0.5 kg substrate; 70% (w/w) moisture content; 30 °C; aeration at 4 L/h.g fermented substrate for 5 min and mixing at 0.5 rpm for 5 min. On the other hand, compared to initial SSF conditions for xylanase production, xylanase activity increased 681% after all factors affect xylanase production have been examined. Conclusion, significance and impact of study: The performance of the newly developed bioreactor is good since it can be used to produce xylanase with high title when compared with previous researcher findings